A polyanion positive electrode material and its preparation method and application
By testing the Na/Fe mixing coefficient of NFPP materials and preparing two sintering methods, the problems of poor electronic conductivity, poor composite phase purity, low compaction density and poor rate performance of NFPP materials were solved, and the high rate performance and cycle stability of the material were achieved.
Patent Information
- Application Number
- CN202411305051.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-09-18
AI Technical Summary
As a sodium-electric polyanionic cathode material, NFPP has problems such as poor electronic conductivity, poor composite phase purity, low compaction density and poor rate performance. Since the Fe ion radius is smaller than that of Na ions, the low sintering temperature leads to misalignment of sodium and iron, which affects the material's cycle stability and rate performance.
By testing the specific capacity of sodium half-cell and lithium half-cell, the Na/Fe mixing coefficient of the polyanionic positive electrode material was determined, and sodium ferric pyrophosphate phosphate material was used, and the secondary sintering temperature was controlled by the preparation method of two sintering to reduce the mixing coefficient and improve the crystallinity and rate performance of the material.
It effectively reduces the Na/Fe mixed displacement situation, improves the rate performance of the battery, improves the material's cycle stability and compaction density, and improves the charging and discharging power performance of the battery.
Smart Images

Figure CN118825268B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of battery positive electrode materials, and relates to a polyanion positive electrode material and a preparation method and application thereof. Background Art
[0002] NFPP(Na 4+x Fe 3-y (PO4)2P2O7) as a phosphate-based sodium cathode material has advantages over layered transition metal oxides, such as excellent cycle stability, high safety, and low structural strain during charge and discharge. However, NFPP has disadvantages such as poor electronic conductivity, poor composite phase purity, low compaction density, and poor rate performance. Therefore, it is necessary to optimize the carbon coating quality of NFPP, improve phase purity, increase compaction density, and improve power performance.
[0003] NFPP is a sodium polyanion cathode material. During the solid phase synthesis process, the sintering temperature is low because the radius of Fe ions is smaller than that of active Na ions. In addition, the NFPP structure is a three-dimensional framework structure, and Na and Fe ions occupy each other. This sodium-iron misalignment will lead to the loss of active Na and the reduction of Fe participating in the redox reaction during the charge and discharge process. If Fe in a more important position occupies the Na position, it will lead to the blockage of multidimensional channels, which is not conducive to the improvement of the material rate performance and the retention of capacity under long cycle conditions. In addition, the low sintering temperature of NFPP makes the material compaction density low, which reduces the charge and discharge power performance of the battery cell, shortens the battery cell life, and reduces the energy density, which is not conducive to the large-scale application of NFPP materials.
[0004] Based on the above research, it is necessary to provide a polyanion positive electrode material, which has a low Na / Fe mixing coefficient and can effectively measure the degree of Na / Fe mutual occupation. Summary of the invention
[0005] The purpose of the present application is to provide a polyanion positive electrode material and a preparation method and application thereof. The Na / Fe mixing coefficient of the polyanion positive electrode material can be determined by the specific capacity of the sodium half-cell and the lithium half-cell, and the polyanion positive electrode material has a low Na / Fe mixing coefficient, which can effectively improve the rate performance of the battery.
[0006] In order to achieve the purpose of this application, this application adopts the following technical solutions:
[0007] In a first aspect, the present application provides a polyanion positive electrode material, the polyanion positive electrode material comprises sodium iron phosphate pyrophosphate material, the Na / Fe mixing coefficient of the polyanion positive electrode material is Mf, and the Mf is ≤0.05;
[0008] The Mf=(CL-CN) / CL, wherein CL is the second cycle discharge specific capacity of the lithium half-cell, and CN is the second cycle discharge specific capacity of the sodium half-cell. The lithium half-cell includes a lithium negative electrode and a pole piece made of the polyanion positive electrode material, and the sodium half-cell includes a sodium negative electrode and a pole piece made of the polyanion positive electrode material.
[0009] The present application can determine the Na / Fe mixing coefficient of the polyanion positive electrode material based on the second cycle discharge specific capacity of the polyanion positive electrode material for lithium half-cell and sodium half-cell, and effectively measure the degree of Na / Fe mutual occupation.
[0010] Preferably, the chemical formula of the sodium iron phosphate pyrophosphate material is Na x M y (PO4) z P2O7, wherein 3.8≤x≤4.2, 2.6≤y≤3, 1.8≤z≤2, and M includes Fe.
[0011] Preferably, the M further includes any one of Mn, Mg, Cr, Cu, Mo, Zn, Zr, Ti, B, Al, Nb or Si, or a combination of at least two thereof.
[0012] Preferably, the molar proportion of Fe in M is ≥90%.
[0013] Preferably, the polyanion positive electrode material further comprises a carbon coating layer, and the carbon coating layer is coated on the surface of the sodium iron phosphate pyrophosphate material.
[0014] Preferably, the compaction density of the polyanion positive electrode material is 1.95 g / cc-2.15 g / cc.
[0015] In a second aspect, the present application provides a method for preparing the polyanion cathode material as described in the first aspect, the preparation method comprising the following steps:
[0016] (1) mixing a sodium source, a phosphorus source and an iron source according to a formula amount to obtain a mixed ingredient;
[0017] (2) mixing and drying the solvent and the mixed ingredients in step (1) to obtain a precursor material, and then sintering the precursor material once to obtain a primary sintered material;
[0018] (3) mixing the mixed ingredients of step (1), the primary sintering material of step (2) and the solvent, drying and performing secondary sintering to obtain the polyanion positive electrode material;
[0019] The secondary sintering temperature is ≤600°C.
[0020] Preferably, in step (3), the mixed ingredients in step (1), the primary sintering material in step (2) and a solvent are mixed, wherein the mass ratio of the mixed ingredients in step (1) to the primary sintering material in step (2) is (0.2-10):1.
[0021] Preferably, in step (3), the mixed ingredients in step (1), the primary sintering material in step (2) and a solvent are mixed, wherein the mass ratio of the mixed ingredients in step (1) to the primary sintering material in step (2) is (0.5-3):1.
[0022] Preferably, in step (3), when the mixed ingredients in step (1), the primary sintering material in step (2) and the solvent are mixed, a carbon source accounting for 1 wt%-10 wt% of the mixed ingredients in step (1) is also added.
[0023] Preferably, the drying methods in step (2) and step (3) are both spray drying, and the spray drying is performed until the moisture content of the dried product is less than 2 wt%.
[0024] Preferably, the mixing methods in step (2) and step (3) are both sand grinding, and the particles are sand ground to a particle size D50 of 0.2 μm-0.6 μm.
[0025] Preferably, the secondary sintering in step (3) is carried out at a temperature of 450°C-600°C and for a time of 2h-10h.
[0026] Preferably, in step (3), air flow crushing is further performed after the secondary sintering, and the air flow crushing is performed to particles with a particle size D50 of 1 μm-4 μm.
[0027] Preferably, in step (3), the mixed ingredients in step (1), the primary sintering material in step (2) and a solvent are mixed to obtain a mixed slurry with a solid content of 25wt%-55wt%.
[0028] Preferably, when the solvent is mixed with the mixed ingredients in step (1) in step (2), a carbon source accounting for 2 wt%-8 wt% of the mixed ingredients in step (1) is also added.
[0029] Preferably, the primary sintering in step (2) is carried out at a temperature of 300°C-600°C and for a time of 2h-10h.
[0030] Preferably, the primary sintering in step (2) includes two heating stages, firstly keeping the temperature at 450-460°C for 4h-7h, and then heating to 530°C-600°C and keeping the temperature for 3h-8h.
[0031] Preferably, in step (2), the solvent is mixed with the mixed ingredients in step (1) to obtain a mixed slurry with a solid content of 15wt%-55wt%.
[0032] In a third aspect, the present application provides a battery, comprising the polyanion positive electrode material as described in the first aspect, or the polyanion positive electrode material prepared by the preparation method described in the second aspect.
[0033] Compared with the prior art, this application has the following beneficial effects:
[0034] (1) In the present application, when the specific capacity of a sodium half-cell is tested by using a polyanion positive electrode material, Na ions are used as migration ions, and what is reflected is the active migration capacity of the Na site in the sodium iron pyrophosphate material, because the Fe ions occupying the Na site will limit the migration of a part of Na, thereby reducing the capacity; when the specific capacity is tested by using a lithium half-cell, Li ions are used as migration ions, and their ion radius is smaller than that of Na ions. Because a part of Na restricted by Fe ions occupying the Na site will still be exchanged by Li ions, thereby releasing capacity. Therefore, the present application can determine the Na / Fe mixing coefficient through the specific capacity of the sodium half-cell and the lithium half-cell.
[0035] (2) The Na / Fe mixing coefficient Mf value described in the present application is relatively small, indicating that the Na / Fe mixing is less, which avoids the mutual occupation of Na / Fe, resulting in the loss of active Na during charging and discharging and the reduction of Fe participating in the redox reaction. It also avoids the problem of multi-dimensional channel blockage caused by Fe occupying the Na position at an important position, thereby reducing the rate performance of the material. Therefore, the polyanion positive electrode material described in the present application has a smaller Na / Fe mixing coefficient, which improves the rate performance Na / Fe of the battery.
[0036] (3) The preparation method described in the present application is prepared by two sinterings to ensure the crystallinity of the particles, thereby ensuring that the product has a low mixing coefficient. Otherwise, the short ion migration distance is likely to lead to poor crystallinity and cause mixing. The temperature of the secondary sintering cannot be too high to ensure that the material is a NFPP phase structure. Otherwise, it will deviate from the structure of the material of the present application, the mixing coefficient will increase significantly, and the rate performance will decrease significantly. In addition, during the secondary sintering, the present application further sinters the mixed ingredients including the sodium source, the phosphorus source and the iron source with the primary sintering material, which can make the mixed ingredients grow on the basis of the first sintering nucleus, thereby further improving the crystallinity and reducing the mixing degree. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a SEM image of the polyanion cathode material described in Example 1 of the present application;
[0038] Figure 2The XRD pattern of the polyanion cathode material described in Example 1 of the present application and the standard XRD pattern of JCPDS (89-0579);
[0039] Figure 3 The charge and discharge curve diagram of the lithium half-cell and the sodium half-cell described in Example 4 of the present application;
[0040] Figure 4 This is a rate performance diagram of the sodium half-battery described in Examples 1-5 and Comparative Examples 1-4 of the present application. DETAILED DESCRIPTION
[0041] The technical solution of the present application is further described below through specific implementation methods. Those skilled in the art should understand that the embodiments are only to help understand the present application and should not be regarded as specific limitations of the present application.
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0043] In a first specific embodiment, the present application provides a polyanion cathode material, the polyanion cathode material includes sodium iron phosphate pyrophosphate material, the Na / Fe mixing coefficient of the polyanion cathode material is Mf, and the Mf is ≤0.05;
[0044] The Mf=(CL-CN) / CL, wherein CL is the second cycle discharge specific capacity of the lithium half-cell, and CN is the second cycle discharge specific capacity of the sodium half-cell. The lithium half-cell includes a lithium negative electrode and a pole piece made of the polyanion positive electrode material, and the sodium half-cell includes a sodium negative electrode and a pole piece made of the polyanion positive electrode material.
[0045] The Na / Fe mixing coefficient Mf mentioned in this application refers to the degree of mutual occupation of Na / Fe. The smaller Mf is, the smaller the degree of mutual occupation of Na / Fe is, and the less Na / Fe mixing is.
[0046] The Na / Fe mixing coefficient Mf value described in the present application is relatively small, indicating that Na / Fe occupies less space with each other, thereby avoiding the loss of active Na during charging and discharging and the reduction of Fe participating in the redox reaction due to the mutual occupation of Na / Fe. It also avoids the problem of multidimensional channel blockage caused by Fe occupying the Na position at an important position, which reduces the rate performance of the material. Therefore, the polyanion positive electrode material described in the present application has a relatively small Na / Fe mixing coefficient, which can reduce the degree of mutual occupation of Na / Fe and improve the rate performance of the battery.
[0047] The present application tests the capacity of half-cells of polyanion positive electrode materials with sodium negative electrode and lithium negative electrode respectively, and the sodium-iron mixing coefficient can be obtained according to the second cycle discharge specific capacity of the test. Specifically, when the sodium half-cell is used to test the specific capacity, Na ions are used as migration ions, which reflect the active migration capacity of the Na site in the sodium iron pyrophosphate material, and the capacity restricted by the Fe ions occupying the Na site cannot be activated; when the lithium half-cell is used to test the specific capacity, Li ions are used as migration ions, which reflect the total migration capacity of the Na site in the sodium iron pyrophosphate material. The radius of Li ions is smaller than that of Na ions, and the atomic weight is lighter. It is easier to break through the energy barrier caused by Fe occupation under the same potential field energy, thereby activating the total gram capacity of the Na site. Therefore, the Na / Fe mixing coefficient Mf value described in the present application can effectively measure the degree of mutual occupation of Na / Fe. According to the formula Mf=(CL-CN) / CL, the smaller the Mf value, the lower the degree of mutual occupation of Na / Fe.
[0048] The Mf≤0.05 may be, for example, 0.05, 0.045, 0.04, 0.035, 0.03, 0.025, 0.02 or 0.015, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 0.015≤Mf≤0.035.
[0049] Preferably, the chemical formula of the sodium iron phosphate pyrophosphate material is Na x M y (PO4) z P2O7, wherein 3.8≤x≤4.2, for example, 3.8, 3.9, 4.0, 4.1 or 4.2, 2.6≤y≤3, for example, 2.6, 2.7, 2.8, 2.9 or 3.0, 1.8≤z≤2, for example, 1.8, 1.9 or 2.0, and M includes Fe.
[0050] Preferably, 3.95≤x≤4.06, 2.7≤y≤2.85, and 1.9≤z≤2.
[0051] Preferably, the M further includes any one of Mn, Mg, Cr, Cu, Mo, Zn, Zr, Ti, B, Al, Nb or Si, or a combination of at least two thereof.
[0052] The sodium iron phosphate pyrophosphate material of the present application also includes doping elements, wherein the selected doping elements are elements with a radius between the Na ion and the Fe ion or elements with a high valence state. At the same time, the use of non-metal-O bond compounds with lower bond energy for doping can reduce the diffusion activation energy of trace elements during low-temperature sintering, and ensure the feasibility of homogeneous doping at a low sintering temperature (<600°C) during the preparation process from a thermodynamic point of view. Homogeneous doping avoids element segregation within the material, and can also enhance the crystal structure stability of the positive electrode material and reduce structural changes during the charge and discharge process, thereby ensuring the cycle stability of the material.
[0053] Preferably, the molar proportion of Fe in M is ≥90%, for example, it can be 90%, 92%, 94%, 96%, 98% or 99%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably ≥95%, further preferably ≥98%, and further preferably ≥99%.
[0054] The Na x M y (PO4) z In P2O7, the molar ratio of Fe in M is ≥90%, which can ensure that doping does not affect the material capacity.
[0055] Preferably, the polyanion positive electrode material further comprises a carbon coating layer, and the carbon coating layer is coated on the surface of the sodium iron phosphate pyrophosphate material.
[0056] The polyanion positive electrode material described in the present application also includes a carbon coating layer, which has good electronic conductivity, can increase the electron transfer rate of the polyanion positive electrode material, reduce the internal resistance of the battery, and can also improve the diffusion path of sodium ions in the positive electrode material, reduce the migration resistance of sodium ions, and improve the rate performance of the battery. At the same time, the carbon coating layer can also serve as a protective layer to improve the chemical stability of the polyanion positive electrode material.
[0057] Preferably, the compaction density of the polyanion positive electrode material is 1.95g / cc-2.15g / cc, for example, it can be 1.95g / cc, 1.97g / cc, 1.99g / cc, 2.11g / cc, 2.13g / cc or 2.15g / cc, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] The polyanion positive electrode material described in the present application has a high compaction density, which can increase the discharge capacity of the battery, reduce internal resistance, and reduce polarization loss. The high compaction density can prevent the electrode particles from falling off during the cycle and form insulating particles, thereby improving the cycle stability of the battery.
[0059] In a second specific embodiment, the present application provides a method for preparing the polyanion cathode material as described in the first specific embodiment, the preparation method comprising the following steps:
[0060] (1) mixing a sodium source, a phosphorus source and an iron source according to a formula amount to obtain a mixed ingredient;
[0061] (2) mixing and drying the solvent and the mixed ingredients in step (1) to obtain a precursor material, and then sintering the precursor material once to obtain a primary sintered material;
[0062] (3) The mixed ingredients of step (1), the primary sintering material of step (2) and the solvent are mixed, dried and secondary sintered to obtain the polyanion positive electrode material.
[0063] The formula quantity in step (1) of the present application refers to the formula quantity of the chemical formula of the sodium iron pyrophosphate material.
[0064] The preparation method described in the present application is to mix the mixed ingredients and the primary sintering materials and perform a secondary sintering, wherein the crystal nuclei formed by the primary sintering are subjected to the secondary sintering, and the product has a higher degree of crystallization and a lower degree of ion mixing, and the mixed ingredients mixed in the secondary sintering process grow on the basis of the crystal nuclei of the primary sintering, which can further improve the crystallinity and reduce the degree of mixing, thereby ensuring that the polyanion positive electrode material has a smaller Mf value; in addition, the preparation method described in the present application requires two sinterings, and the temperature of the secondary sintering needs to be ≤600°C to ensure that the polyanion positive electrode material has a smaller Mf value. If only one sintering is performed, the low heat treatment temperature and the short ion migration distance can easily lead to poor crystallinity, causing mixing, making the Mf value higher or even component segregation. If the temperature of the secondary sintering exceeds 600°C, it will cause PO4 to lose oxygen and excessive generation of P2O7 phase, and the material will significantly deviate from the NFPP phase structure, that is, it will deviate from the structure of the material of the present application, and the mixing coefficient will be significantly increased, thereby significantly reducing the rate performance.
[0065] The present application achieves a grading effect by mixing the primary sintering material with the mixed ingredients and then performing a secondary sintering, which significantly improves the compaction density of the polyanion positive electrode material, and can produce small particles in the secondary sintering. The production of small particles reduces the ion migration distance, thereby improving the rate performance of the polyanion positive electrode material.
[0066] Preferably, in step (3), the mixed ingredients of step (1), the primary sintering material of step (2) and the solvent are mixed, wherein the mass ratio of the mixed ingredients of step (1) to the primary sintering material of step (2) is (0.2-10):1, for example, it can be 0.2:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1 or 10:1, but is not limited to the listed values, and other values not listed within the numerical range are also applicable, preferably (0.5-3):1.
[0067] The mass ratio of the mixed ingredients in step (1) of the present application to the primary sintered material in step (2) will affect the grading effect and the ion migration distance, thereby affecting the compaction density and rate performance of the polyanion positive electrode material; and when the mass ratio of the mixed ingredients in the present application to the primary sintered material in step (2) is between (0.2-10):1, the ratio of the seed crystal to the raw material in the NFPP phase secondary sintering process is relatively suitable, preferably (0.5-3):1, at this time, the adaptability to the secondary sintering process is stronger and a higher degree of crystallization can be obtained, thereby effectively reducing the degree of mixing.
[0068] Preferably, in step (3), when mixing the mixed ingredients of step (1), the primary sintering material of step (2) and the solvent, a carbon source accounting for 1wt%-10wt% of the mixed ingredients of step (1) is also added, for example, it can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0069] The present application carries out coating twice in total, and the secondary carbon coating is performed during the mixing of the materials in the above step (3). The secondary carbon coating can improve the electronic conductivity of the polyanion positive electrode material and also contribute to the improvement of the rate.
[0070] Preferably, the drying methods in step (2) and step (3) are both spray drying, and the moisture content of the dried product is less than 2wt%, for example, 2wt%, 1.5wt%, 1.0wt% or 0.5wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0071] Preferably, the mixing method in step (2) and step (3) is sand grinding, and the particle size D50 of the particles is 0.2μm-0.6μm, for example, it can be 0.2μm, 0.3μm, 0.4μm, 0.5μm or 0.6μm. When sand grinding is performed in step (2), the particle size D50 of the particles is 0.3μm-0.6μm, for example, it can be 0.3μm, 0.4μm, 0.5μm or 0.6μm, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0072] The present application can effectively improve the stability of the process through two sand grindings, two spray dryings and two sinterings. Among them, the sand grinding of the primary sintering material can effectively reduce the problem of looseness between particles of different raw materials caused by the spray granulation process. The two spray dryings are respectively performed before the two sinterings, which can obtain evenly distributed and highly dispersed particles, which is beneficial to the subsequent sintering.
[0073] Preferably, the temperature of the secondary sintering in step (3) is 450°C-600°C, for example, 450°C, 500°C, 550°C or 600°C, but is not limited to the listed values. Other values not listed within the numerical range are also applicable, preferably 520°C-570°C.
[0074] As mentioned above, if the secondary sintering temperature of the present application is too high, the material will significantly deviate from the NFPP phase structure, and the increase in the value of the mixing coefficient can be clearly observed. The secondary sintering temperature used in the present application is 450℃-600℃, which can ensure the effect of the secondary sintering.
[0075] Preferably, the secondary sintering time in step (3) is 2 h-10 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, but is not limited to the listed values. Other values not listed within the numerical range are also applicable, preferably 6 h-9 h.
[0076] Preferably, the secondary sintering in step (3) is carried out in a protective atmosphere with a purity greater than 99.99%, wherein the protective atmosphere comprises nitrogen.
[0077] Preferably, in step (3), air flow crushing is further performed after the secondary sintering, and the particle size D50 of the particles crushed by the air flow is 1 μm-4 μm, for example, it can be 1 μm, 2 μm, 3 μm or 4 μm, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0078] Preferably, in step (3), the mixed ingredients in step (1), the primary sintering material in step (2) and the solvent are mixed to obtain a mixed slurry with a solid content of 25wt%-55wt%, for example, 25wt%, 35wt%, 45wt% or 55wt%, but not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0079] Preferably, when the solvent is mixed with the mixed ingredients in step (1) in step (2), a carbon source accounting for 2wt%-8wt% of the mixed ingredients in step (1) is also added, for example, it can be 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt% or 8wt%, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0080] Preferably, when the solvent is mixed with the mixed ingredients in step (1) in step (2), a formulated amount of doping source is also added.
[0081] Preferably, the primary sintering temperature in step (2) is 300°C-600°C, for example, 300°C, 400°C, 500°C or 600°C, and the time is 2h-10h, for example, 2h, 4h, 6h, 8h or 10h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0082] The primary sintering in step (2) of the present application includes two heating stages, such as first at 450°C-460°C, such as 450°C, 455°C or 460°C, keeping warm for 4h-7h, such as 4h, 5h, 6h or 7h, and then heating to 530°C-600°C, such as 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C or 600°C, and keeping warm for 3h-8h, such as 3h, 5h, 7h or 8h. The two heating stages of the primary sintering can realize the sintering of the mixed ingredients in the precursor material and coating the carbon source.
[0083] Preferably, in step (2), the solvent is mixed with the mixed ingredients in step (1) to obtain a mixed slurry with a solid content of 15wt%-55wt%, for example, 15wt%, 25wt%, 35wt%, 45wt% or 55wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0084] Preferably, the sodium source in step (1) comprises any one of sodium carbonate, sodium bicarbonate, sodium oxalate, sodium acetate, sodium dihydrogen phosphate, sodium monohydrogen phosphate, sodium pyrophosphate or sodium dihydrogen pyrophosphate, or a combination of at least two thereof.
[0085] Preferably, the iron source in step (1) comprises any one of iron, ferric oxide, ferrous oxide, ferrous oxalate, ferric phosphate or ferric nitrate, or a combination of at least two thereof.
[0086] Preferably, the phosphorus source in step (1) includes any one of phosphoric acid, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, ferric phosphate, sodium pyrophosphate or sodium dihydrogen pyrophosphate, or a combination of at least two thereof.
[0087] Preferably, a doping source is also added during the preparation of the ingredients in step (1).
[0088] In the mixing step (1) of this application, according to the chemical formula Na x M y (PO4) z P2O7 is mixed.
[0089] Preferably, the doping source includes any one of oxalate, phosphate, nitrate, carbonate, sulfate, ammonium salt or an organic compound thereof, or a combination of at least two thereof.
[0090] The carbon source described in the present application includes any one of citric acid, oxalic acid, ascorbic acid, glucose, sucrose, fructose, polyethylene glycol, starch, carboxymethyl cellulose polyethylene, polypropylene, polystyrene, polyacrylonitrile, carboxymethyl cellulose, chitosan, maltodextrin, phenolic resin, epoxy resin or urea-formaldehyde resin, or a combination of at least two thereof.
[0091] The solvent described in the present application includes deionized water.
[0092] In a third specific embodiment, the present application provides a battery, which includes the polyanion cathode material as described in the first specific embodiment or the polyanion cathode material prepared by the preparation method as described in the second specific embodiment.
[0093] It should be noted that the present application does not specifically limit the type of battery provided, for example, it can be a lithium-ion battery or a sodium-ion battery.
[0094] The battery provided in the present application includes a positive electrode plate containing a polyanion positive electrode material, and may also include a negative electrode plate, an electrolyte and a separator (the separator is optional).
[0095] Preferably, the positive electrode plate comprises a positive electrode current collector and an active material layer coated on at least one side of the positive electrode current collector, and the active material layer comprises the polyanion positive electrode material, positive electrode binder and positive electrode conductor described in the first specific embodiment.
[0096] Preferably, the positive electrode binder includes any one or a combination of at least two of polyvinylidene fluoride, polytetrafluoroethylene, polyethylene glycol, polyimide, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile or polyacrylate. Those skilled in the art can select according to needs, and no specific limitation is made here.
[0097] Preferably, the positive electrode conductive agent includes any one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers, or a combination of at least two thereof. Those skilled in the art may select the one according to their needs, and no specific limitation is made here.
[0098] Preferably, the negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer covering the surface of the negative electrode current collector.
[0099] Preferably, the negative electrode active material layer includes a negative electrode binder, a negative electrode active material and a negative electrode conductor.
[0100] Preferably, the negative electrode binder includes any one of polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyvinylidene fluoride, nitrile rubber, styrene-ethylene-butylene-styrene copolymer, styrene-butadiene-styrene copolymer, lithium polyacrylate, sodium polyacrylate, sodium alginate or lithium alginate, or a combination of at least two thereof. Those skilled in the art can select the one according to their needs, and no specific limitation is made here.
[0101] Preferably, the negative electrode active material includes any one of graphite, soft carbon, hard carbon, silicon oxygen or silicon carbon, or a combination of at least two thereof. Those skilled in the art may select the material according to their needs, and no specific limitation is made here.
[0102] Preferably, the negative electrode conductive agent includes any one of conductive carbon black, carbon nanotubes, vapor-grown carbon nanotubes or nano-carbon fibers, or a combination of at least two of them. Those skilled in the art can select according to needs, and no specific limitation is made here.
[0103] Preferably, the present application does not specifically limit the type of electrolyte, and any known electrolyte material can be used in the present application without violating the concept of the present application. As an illustrative example, the electrolyte can be a liquid electrolyte, a solid electrolyte, or a mixture of a solid electrolyte and a liquid electrolyte.
[0104] In addition, the electrolyte used in the present application may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc., which can be used in the manufacture of a secondary battery, but is not limited thereto.
[0105] Preferably, the electrolyte can be a solid electrolyte, and the solid electrolyte particles can contain any one or a combination of at least two of one or more polymer components, oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, borate solid electrolytes, nitride solid electrolytes or hydride solid electrolytes. Those skilled in the art can choose according to needs, and no specific limitation is made here.
[0106] Specifically, the electrolyte may include an organic solvent and a lithium salt (or a sodium salt).
[0107] Any organic solvent can be used in the electrolyte without particular limitation, as long as it can serve as a medium through which ions participating in the electrochemical reaction of the battery can move; for example, as the organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and E-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl methyl carbonate, ethylene carbonate and propylene carbonate; alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (wherein R is a linear, branched or cyclic C2-C20 hydrocarbon group, and may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or cyclopentane sulfone.
[0108] Any compound can be used as the lithium salt without particular limitation, as long as it can provide the lithium ions used in the lithium secondary battery. For example, the lithium salt source includes but is not limited to any one of LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4 or LiCF3SO3, or a combination of at least two thereof.
[0109] Any compound can be used as the sodium salt without particular limitation, as long as it can provide the sodium ions used in the sodium secondary battery, for example, the sodium salt includes but is not limited to any one of sodium perchlorate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium trifluoroacetate, sodium difluorophosphate, sodium tetraphenylborate, sodium trifluoromethylsulfonate, sodium bis(fluorosulfonyl)imide) or sodium bis(trifluoromethylsulfonyl)imide or a combination of at least two thereof.
[0110] Preferably, the main function of the separator is to separate the negative electrode from the positive electrode and provide a path for the movement of lithium ions (or sodium ions). Any separator can be used without particular limitation, as long as it is a separator commonly used in secondary batteries. In particular, a separator with excellent electrolyte wettability and low resistance to ion movement in the electrolyte is preferred. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer and an ethylene / methacrylate copolymer, or a laminated structure having more than two layers thereof. In addition, a typical porous non-woven fabric can be used, for example, a non-woven fabric formed of glass fiber, polyethylene terephthalate fiber, etc. having a high melting point. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single-layer or multilayer structure.
[0111] The technical solution of the present application is further illustrated by means of specific embodiments below. Example 1
[0112] This embodiment provides a polyanion positive electrode material, wherein the polyanion positive electrode material comprises a sodium ferric phosphate pyrophosphate material and a carbon coating layer on the surface of the sodium ferric phosphate pyrophosphate material, wherein the sodium ferric phosphate pyrophosphate material comprises Na 4.04 M 2.83 (PO4)2P2O7, M includes Fe, Mg and Al, wherein the molar proportion of Fe in M is 97.85%, the molar proportion of Mg is 1.34%, and the molar proportion of Al is 0.81%;
[0113] The Na / Fe mixing coefficient of the polyanion positive electrode material is Mf, and Mf=(CL-CN) / CL=0.0272, wherein CL is the second cycle discharge specific capacity of the lithium half-cell, and CN is the second cycle discharge specific capacity of the sodium half-cell. The lithium half-cell includes a lithium negative electrode and a pole piece made of the polyanion positive electrode material, and the sodium half-cell includes a sodium negative electrode and a pole piece made of the polyanion positive electrode material.
[0114] The preparation method of the polyanion positive electrode material comprises the following steps:
[0115] (1) Mixing sodium dihydrogen phosphate dihydrate, anhydrous ferrous oxalate, magnesium nitrate and aluminum sulfate according to the formula amount to obtain a mixed ingredient;
[0116] (2) Deionized water, the mixed ingredients of step (1) and glucose accounting for 8 wt% of the mixed ingredients of step (1) are mixed to obtain a mixed slurry with a solid content of 30 wt%, the mixed slurry is coarsely ground for 1 hour, and then sand-milled for 1.2 hours to make the particle size D50 in the mixed slurry 0.35 μm, and then the mixed slurry is spray-dried once, and the outlet air temperature is controlled to be 95° C. during the spray drying, to obtain a precursor material;
[0117] The precursor material is heated to 460° C. at a heating rate of 2° C. / min, kept at this temperature for 4 hours, and then heated to 600° C. and kept at this temperature for 4 hours, and sintered once to obtain a primary sintered material;
[0118] (3) mixing the mixed ingredients of step (1), the primary sintering material of step (2), glucose accounting for 8 wt% of the mixed ingredients of step (1), and deionized water, wherein the mass ratio of the mixed ingredients of step (1) to the primary sintering material of step (2) is 1:1, to obtain a mixed slurry with a solid content of 35 wt%;
[0119] The mixed slurry was coarsely ground for 1 hour and then sand-milled for 1.2 hours to make the particle size D50 in the mixed slurry 0.3 μm. The mixed slurry was then spray-dried for a second time, with the outlet air temperature controlled at 95°C during the second spray drying. The mixed slurry was then sintered for a second time at 550°C for 8 hours in a nitrogen atmosphere to obtain the polyanion positive electrode material.
[0120] The SEM image of the polyanion positive electrode material described in this embodiment is as follows Figure 1 As shown, the XRD pattern of the polyanion positive electrode material described in this embodiment and the JCPDS (89-0579) standard XRD pattern are as follows Figure 2 As shown in JCPDS (89-0579), the XRD standard diagram of sodium iron pyrophosphate is Figure 2 It can be seen that the polyanion cathode material obtained in this example is consistent with the crystal structure of the JCPDS (89-0579) standard spectrum, indicating that the polyanion cathode material obtained in this example is a NFPP material. Example 2
[0121] This embodiment provides a polyanion positive electrode material, wherein the polyanion positive electrode material comprises a sodium ferric phosphate pyrophosphate material and a carbon coating layer on the surface of the sodium ferric phosphate pyrophosphate material, wherein the sodium ferric phosphate pyrophosphate material comprises Na 4.02 M 2.75 (PO4) 1.83 P2O7, M includes Fe and B, wherein the molar proportion of Fe in M is 99.02%, and the molar proportion of B is 0.98%;
[0122] The Na / Fe mixing coefficient of the polyanion positive electrode material is Mf, and Mf=(CL-CN) / CL=0.0164, wherein CL is the second cycle discharge specific capacity of the lithium half-cell, and CN is the second cycle discharge specific capacity of the sodium half-cell. The lithium half-cell includes a lithium negative electrode and a pole piece made of the polyanion positive electrode material, and the sodium half-cell includes a sodium negative electrode and a pole piece made of the polyanion positive electrode material.
[0123] The preparation method of the polyanion positive electrode material comprises the following steps:
[0124] (1) Mixing sodium dihydrogen phosphate dihydrate, anhydrous ferrous oxalate and boric oxide according to the formula amount to obtain a mixed ingredient;
[0125] (2) Mixing deionized water, the mixed ingredients of step (1), 5 wt% of glucose and 4 wt% of PEG4000 to obtain a mixed slurry with a solid content of 25 wt%, coarsely grinding the mixed slurry for 1 hour, and then sand grinding for 0.8 hour to make the particle size D50 of the mixed slurry 0.37 μm, and then spray drying the mixed slurry once, controlling the outlet air temperature to 97 ° C during the spray drying, to obtain a precursor material;
[0126] The precursor material is heated to 450° C. at a heating rate of 3° C. / min, kept at this temperature for 7 hours, and then heated to 560° C. and kept at this temperature for 3 hours, and sintered once to obtain a primary sintered material;
[0127] (3) mixing the mixed ingredients of step (1), the primary sintering material of step (2), 5 wt% of glucose in the mixed ingredients of step (1), 4 wt% of PEG4000 in the mixed ingredients of step (1), and deionized water, wherein the mass ratio of the mixed ingredients of step (1) to the primary sintering material of step (2) is 1:1, to obtain a mixed slurry with a solid content of 55 wt%;
[0128] The mixed slurry was coarsely ground for 1 hour and then sand-milled for 1.5 hours to make the particle size D50 in the mixed slurry 0.27 μm. The mixed slurry was then spray-dried for a second time, with the outlet air temperature controlled at 95°C during the second spray drying. The mixed slurry was then sintered for a second time at 560°C for 8 hours in a nitrogen atmosphere to obtain the polyanion positive electrode material. Example 3
[0129] This embodiment provides a polyanion positive electrode material, wherein the polyanion positive electrode material comprises a sodium ferric phosphate pyrophosphate material and a carbon coating layer on the surface of the sodium ferric phosphate pyrophosphate material, wherein the sodium ferric phosphate pyrophosphate material comprises Na 4.03 M 2.82(PO4)2P2O7, M includes Fe and Zr, wherein the molar proportion of Fe in M is 99.82%, and the molar proportion of Zr is 0.18%;
[0130] The Na / Fe mixing coefficient of the polyanion positive electrode material is Mf, and Mf=(CL-CN) / CL=0.0255, wherein CL is the second cycle discharge specific capacity of the lithium half-cell, and CN is the second cycle discharge specific capacity of the sodium half-cell. The lithium half-cell includes a lithium negative electrode and a pole piece prepared from the polyanion positive electrode material, and the sodium half-cell includes a sodium negative electrode and a pole piece prepared from the polyanion positive electrode material.
[0131] The preparation method of the polyanion positive electrode material comprises the following steps:
[0132] (1) Mixing sodium pyrophosphate, ferric phosphate, ferric oxide and zirconium chloride according to the formula amount to obtain a mixed ingredient;
[0133] (2) Mixing deionized water, the mixed ingredients of step (1), 5 wt% of glucose and 4 wt% of PEG4000 to obtain a mixed slurry with a solid content of 25 wt%, coarsely grinding the mixed slurry for 1 hour, and then sand grinding for 0.8 hour to make the particle size D50 of the mixed slurry 0.37 μm, and then spray drying the mixed slurry once, controlling the outlet air temperature to 97 ° C during the spray drying, to obtain a precursor material;
[0134] The precursor material is heated to 460° C. at a heating rate of 3° C. / min, kept at this temperature for 5 hours, and then heated to 530° C. and kept at this temperature for 8 hours, and sintered once to obtain a primary sintered material;
[0135] (3) mixing the mixed ingredients of step (1), the primary sintering material of step (2), 5 wt% of glucose in the mixed ingredients of step (1), 4 wt% of PEG4000 in the mixed ingredients of step (1), and deionized water, wherein the mass ratio of the mixed ingredients of step (1) to the primary sintering material of step (2) is 2:1, to obtain a mixed slurry with a solid content of 25 wt%;
[0136] The mixed slurry was coarsely ground for 1 hour and then sand-milled for 0.8 hour to make the particle size D50 in the mixed slurry 0.37 μm. The mixed slurry was then spray-dried for a second time, with the outlet air temperature controlled at 95°C during the second spray drying. The mixed slurry was then sintered for a second time at 560°C for 8 hours in a nitrogen atmosphere to obtain the polyanion positive electrode material. Example 4
[0137] This embodiment provides a polyanion positive electrode material, wherein the polyanion positive electrode material comprises a sodium ferric phosphate pyrophosphate material and a carbon coating layer on the surface of the sodium ferric phosphate pyrophosphate material, wherein the sodium ferric phosphate pyrophosphate material comprises Na 4.02 M 2.62 (PO4) 1.78 P2O7, M includes Fe and Nb, wherein the molar proportion of Fe in M is 99.73%, and the molar proportion of Nb is 0.27%;
[0138] The Na / Fe mixing coefficient of the polyanion positive electrode material is Mf, and Mf=(CL-CN) / CL=0.0205, wherein CL is the second cycle discharge specific capacity of the lithium half-cell, and CN is the second cycle discharge specific capacity of the sodium half-cell. The lithium half-cell includes a lithium negative electrode and a pole piece prepared from the polyanion positive electrode material, and the sodium half-cell includes a sodium negative electrode and a pole piece prepared from the polyanion positive electrode material.
[0139] The preparation method of the polyanion positive electrode material comprises the following steps:
[0140] (1) Mixing sodium pyrophosphate, ferric phosphate, ferric oxide and niobium chloride according to the formula amount to obtain a mixed ingredient;
[0141] (2) Mixing deionized water, the mixed ingredients of step (1), 5 wt% of glucose and 4 wt% of PEG4000 to obtain a mixed slurry with a solid content of 25 wt%, coarsely grinding the mixed slurry for 1 hour, and then sand grinding for 0.8 hour to make the particle size D50 of the mixed slurry 0.37 μm, and then spray drying the mixed slurry once, controlling the outlet air temperature to 97 ° C during the spray drying, to obtain a precursor material;
[0142] The precursor material is heated to 460° C. at a heating rate of 3° C. / min, kept at this temperature for 4 hours, and then heated to 540° C. and kept at this temperature for 6 hours, and sintered once to obtain a primary sintered material;
[0143] (3) mixing the mixed ingredients of step (1), the primary sintering material of step (2), 5 wt% of glucose in the mixed ingredients of step (1), 4 wt% of PEG4000 in the mixed ingredients of step (1), and deionized water, wherein the mass ratio of the mixed ingredients of step (1) to the primary sintering material of step (2) is 0.5:1, to obtain a mixed slurry with a solid content of 25 wt%;
[0144] The mixed slurry was coarsely ground for 1 hour and then sand-milled for 1 hour to make the particle size D50 in the mixed slurry 0.32 μm. The mixed slurry was then spray-dried for a second time, and the outlet air temperature was controlled to be 95° C. during the second spray drying. The mixed slurry was then sintered for a second time at 560° C. for 8 hours in a nitrogen atmosphere to obtain the polyanion positive electrode material.
[0145] The charge and discharge curves of the lithium half-cell and the sodium half-cell described in this embodiment are as follows: Figure 3 shown. Example 5
[0146] This embodiment provides a polyanion positive electrode material, wherein the polyanion positive electrode material comprises a sodium ferric phosphate pyrophosphate material and a carbon coating layer on the surface of the sodium ferric phosphate pyrophosphate material, wherein the sodium ferric phosphate pyrophosphate material comprises Na 3.91 M 2.63 (PO4) 1.85 P2O7, M includes Fe, Ti and Nb, wherein the molar proportion of Fe in M is 99.54%, the molar proportion of Ti is 0.31%, and the molar proportion of Nb is 0.15%;
[0147] The Na / Fe mixing coefficient of the polyanion positive electrode material is Mf, and Mf=(CL-CN) / CL=0.0346, wherein CL is the second cycle discharge specific capacity of the lithium half-cell, and CN is the second cycle discharge specific capacity of the sodium half-cell. The lithium half-cell includes a lithium negative electrode and a pole piece prepared from the polyanion positive electrode material, and the sodium half-cell includes a sodium negative electrode and a pole piece prepared from the polyanion positive electrode material;
[0148] The preparation method of the polyanion positive electrode material comprises the following steps:
[0149] (1) Sodium pyrophosphate, ferric phosphate, ferric oxide, titanium tetrachloride and niobium chloride are mixed according to the formula amount to obtain a mixed ingredient;
[0150] (2) Deionized water, the mixed ingredients of step (1), 5 wt% of glucose and 4 wt% of PEG4000 are mixed to obtain a mixed slurry with a solid content of 25 wt%, the mixed slurry is coarsely ground for 1 hour, and then sand-milled for 0.8 hour to make the particle size D50 of the mixed slurry 0.34 μm, and then the mixed slurry is spray-dried once, and the outlet air temperature is controlled to be 97° C. during the spray drying, to obtain a precursor material;
[0151] The precursor material is heated to 450° C. at a heating rate of 3° C. / min, kept at this temperature for 7 hours, and then heated to 540° C. and kept at this temperature for 5 hours, and sintered once to obtain a primary sintered material;
[0152] (3) mixing the mixed ingredients of step (1), the primary sintering material of step (2), 5 wt% of glucose in the mixed ingredients of step (1), 4 wt% of PEG4000 in the mixed ingredients of step (1), and deionized water, wherein the mass ratio of the mixed ingredients of step (1) to the primary sintering material of step (2) is 3:1, to obtain a mixed slurry with a solid content of 25 wt%;
[0153] The mixed slurry was coarsely ground for 1 hour and then sand-milled for 1 hour to make the particle size D50 in the mixed slurry 0.34 μm. The mixed slurry was then spray-dried for a second time, and the outlet air temperature was controlled to be 95°C during the second spray drying. The mixed slurry was then sintered for a second time at 570°C for 8 hours in a nitrogen atmosphere to obtain the polyanion positive electrode material. Example 6
[0154] This embodiment provides a polyanion positive electrode material, which is the same as that of Embodiment 1 except that Mf=0.0347 and in the preparation method thereof, the mass ratio of the mixed ingredients in step (1) to the primary sintered material in step (2) is 0.2:1, so that the adaptability of the obtained polyanion positive electrode material changes. Example 7
[0155] The present embodiment provides a polyanion positive electrode material, which is the same as that of the embodiment 1 except that Mf=0.0415 and in the preparation method thereof, the mass ratio of the mixed ingredients in step (1) to the primary sintered material in step (2) is 5:1, so that the adaptability of the obtained polyanion positive electrode material is changed. Example 8
[0156] This embodiment provides a polyanion positive electrode material, which is the same as that of Embodiment 1 except that Mf=0.0446 and in the preparation method thereof, the mass ratio of the mixed ingredients in step (1) to the primary sintered material in step (2) is 10:1, so that the adaptability of the obtained polyanion positive electrode material is changed. Example 9
[0157] The present embodiment provides a polyanion positive electrode material, which is the same as that of the embodiment 1 except that Mf=0.0495 and in the preparation method thereof, the mass ratio of the mixed ingredients in step (1) to the primary sintered material in step (2) is 12:1, so that the adaptability of the obtained polyanion positive electrode material is changed. Example 10
[0158] The present embodiment provides a polyanion cathode material, which is the same as that of embodiment 1 except that Mf=0.0406 and in the preparation method thereof, the glucose in step (3) is added during the mixing and preparing of the mixed slurry in step (2), so that the glucose added in step (2) accounts for 16 wt % of the mixed ingredients in step (1), thereby changing the adaptability of the obtained polyanion cathode material. Embodiment 11
[0159] This embodiment provides a polyanion positive electrode material, which is the same as that of Embodiment 1 except that Mf=0.0339 and in the preparation method thereof, the temperature of the secondary sintering in step (3) is 450° C. to make the polyanion positive electrode material adaptable. Example 12
[0160] This embodiment provides a polyanion positive electrode material, which is the same as that of Embodiment 1 except that Mf=0.0483 and in the preparation method thereof, the temperature of the secondary sintering in step (3) is 600° C. to make the polyanion positive electrode material adaptable. Example 13
[0161] This embodiment provides a polyanion positive electrode material. The polyanion positive electrode material includes Na 4.04 Fe 2.83 (PO4)2P2O7, M does not contain other elements, Mf=0.0332, and in the preparation method thereof, step (1) is the same as Example 1 except that sodium dihydrogen phosphate dihydrate and anhydrous ferrous oxalate are mixed according to the formula amount to obtain a mixed ingredient, so that the adaptability of the obtained polyanion positive electrode material is changed.
[0162] Comparative Example 1
[0163] This comparative example provides a polyanion positive electrode material, the polyanion positive electrode material includes a sodium ferric phosphate pyrophosphate material and a carbon coating layer on the surface of the sodium ferric phosphate pyrophosphate material, the sodium ferric phosphate pyrophosphate material includes Na 4.06 M 2.75 (PO4)2P2O7, M includes Fe and Co, wherein the molar proportion of Fe in M is 99.53%, and the molar proportion of Co is 0.47%;
[0164] The Na / Fe mixing coefficient of the polyanion positive electrode material is Mf, and Mf=(CL-CN) / CL=0.0647, wherein CL is the second cycle discharge specific capacity of the lithium half-cell, and CN is the second cycle discharge specific capacity of the sodium half-cell. The lithium half-cell includes a lithium negative electrode and a pole piece made of the polyanion positive electrode material, and the sodium half-cell includes a sodium negative electrode and a pole piece made of the polyanion positive electrode material.
[0165] The preparation method of the polyanion positive electrode material comprises the following steps:
[0166] (1) mixing phosphoric acid, sodium carbonate, iron oxide and cobalt chloride according to the formula amount to obtain a mixed ingredient;
[0167] (2) Deionized water, the mixed ingredients of step (1), 5 wt% of glucose and 4 wt% of PEG4000 are mixed to obtain a mixed slurry with a solid content of 30 wt%, the mixed slurry is coarsely ground for 1 h, and then sand-milled for 1.2 h to make the particle size D50 of the mixed slurry 0.36 μm, and then the mixed slurry is spray-dried once, and the outlet air temperature is controlled to be 95° C. during the spray-drying, to obtain a precursor material;
[0168] The precursor material is heated to 450° C. at a heating rate of 3° C. / min, kept at this temperature for 7 hours, and then heated to 560° C. and kept at this temperature for 3 hours, and sintered once to obtain the polyanion positive electrode material.
[0169] Comparative Example 2
[0170] This comparative example provides a polyanion positive electrode material, which is the same as Example 1 except that Mf=0.0608 and in its preparation method, the precursor material in step (2) is directly sintered at 560°C for 8h without step (3) to make the adaptability of the obtained polyanion positive electrode material change.
[0171] Comparative Example 3
[0172] This comparative example provides a polyanion positive electrode material, which is the same as Example 1 except that Mf=0.0583 and in its preparation method, the mixed ingredients described in step (1) are not added in step (3) to change the adaptability of the obtained polyanion positive electrode material.
[0173] Comparative Example 4
[0174] This comparative example provides a polyanion positive electrode material, which is the same as Example 1 except that Mf=0.3276 and in the preparation method thereof, the temperature of the secondary sintering in step (3) is 670°C to make the adaptability of the obtained polyanion positive electrode material change.
[0175] Comparative Example 5
[0176] This comparative example provides a polyanion positive electrode material, which is the same as Example 1 except that Mf=0.288 and in the preparation method thereof, the temperature of the secondary sintering in step (3) is 650°C to make the adaptability of the obtained polyanion positive electrode material change.
[0177] The test method for the compaction density of the polyanion positive electrode material described in the above embodiments and comparative examples is: using a powder compaction density instrument, taking a sample of 0.8-1.5g, applying a 13mm diameter mold, a pressure of 3T, maintaining the pressure for 30s, and automatically calculating the compaction density under a pressure of 3T through the instrument.
[0178] The preparation method of the lithium half-cell described in the above embodiments and comparative examples includes: homogenizing according to the ratio of active material: conductive carbon black sp: binder PDVF = 8:1:1, coating a single-sided surface density of 10 mg / cm2, drying at 120°C for 12 hours, using a lithium sheet as the negative electrode, using 1 mol / L LiPF6 lithium battery electrolyte, and assembling a 2032 button half-cell; The preparation method of the sodium half-cell includes: homogenizing according to the ratio of active material: conductive carbon black sp: binder PDVF = 8:1:1, coating a single-sided surface density of 10 mg / cm 2 , dried at 120℃ for 12 hours, the negative electrode uses sodium sheet, 1mol / L NaPF6 sodium electrolyte, and assembles 2032 button half-cell.
[0179] The second cycle discharge specific capacity CL and CN of the lithium half-cell and the sodium half-cell were tested at 25°C, and the gram capacity at different rates was tested. The electrochemical performance test results and the compaction density and Mf of the polyanion positive electrode material are shown in Table 1. The rate performance diagram of the sodium half-cell described in Examples 1-5 and Comparative Examples 1-4 is shown in Figure 4 As shown by Figure 4 It can be seen that the gram capacity of Examples 1-5 of the present application at different rates is basically higher than that of Comparative Examples 1-4, especially the gram capacity at high rates such as 10C is significantly higher than that of Comparative Examples 1-4, indicating that the polyanion positive electrode materials obtained in Examples 1-5 of the present application have excellent rate performance.
[0180] Table 1
[0181]
[0182] From Table 1 we can see that:
[0183] The polyanion cathode material described in the present application has a smaller mixing coefficient, which is beneficial to improving the rate performance of the battery; it can be seen from Examples 1-5 and Comparative Examples 1-3 that the present application can improve the particle grading effect of the product and reduce the Mf value by performing a secondary sintering together with the mixed ingredients and the primary sintering material, thereby helping to improve the rate performance of the battery; it can be seen from Examples 1-5, Examples 11-12 and Comparative Examples 4-5 that if the secondary sintering temperature is too high, PO4 will lose oxygen, P2O7 phase will be excessively generated, the material will significantly deviate from the NFPP phase structure, and the rate performance will significantly decrease, and its value can be clearly observed to increase from the mixing coefficient; it can be seen from Examples 1 and 6-9 that the mass ratio of the mixed ingredients and the primary sintering material of the present application will affect the grading effect, thereby affecting the rate performance of the battery; it can be seen from Examples 1 and 10 that the secondary carbon coating of the present application will affect the electronic conductivity of the material, thereby affecting the improvement of the battery rate; it can be seen from Examples 1 and 13 that the polyanion cathode material described in the present application may not contain doping elements.
[0184] In summary, the present application provides a polyanion positive electrode material and a preparation method and application thereof. The Na / Fe mixing coefficient of the polyanion positive electrode material can be determined by the specific capacity of the sodium half-cell and the lithium half-cell, and the polyanion positive electrode material has a low Na / Fe mixing coefficient, which can effectively improve the rate performance of the battery.
[0185] The above description is only a specific implementation manner of the present application, but the protection scope of the present application is not limited thereto. Technicians in the relevant technical field should understand that any changes or substitutions that can be easily thought of by technicians in the relevant technical field within the technical scope disclosed in the present application are within the protection scope and disclosure scope of the present application.
Claims
1. A polyanion positive electrode material, characterized in that: The polyanion positive electrode material comprises sodium iron phosphate pyrophosphate material, and the Na / Fe mixing coefficient of the polyanion positive electrode material is Mf, 0.0164≤Mf≤0.05; The Mf=(CL-CN) / CL, wherein CL is the second cycle discharge specific capacity of the lithium half-cell, and CN is the second cycle discharge specific capacity of the sodium half-cell. The lithium half-cell includes a lithium negative electrode and a pole piece made of the polyanion positive electrode material, and the sodium half-cell includes a sodium negative electrode and a pole piece made of the polyanion positive electrode material. The preparation method of the polyanion positive electrode material comprises the following steps: (1) mixing a sodium source, a phosphorus source and an iron source according to a formula amount to obtain a mixed ingredient; (2) mixing and drying the solvent and the mixed ingredients in step (1) to obtain a precursor material, and then sintering the precursor material once to obtain a primary sintered material; (3) mixing the mixed ingredients of step (1), the primary sintering material of step (2) and the solvent, drying and performing secondary sintering to obtain the polyanion positive electrode material; The secondary sintering temperature is ≤600°C.
2. The polyanion positive electrode material according to claim 1, characterized in that The chemical formula of the sodium iron phosphate pyrophosphate material is Na x M y (PO4) z P2O7, wherein 3.8≤x≤4.2, 2.6≤y≤3, 1.8≤z≤2, and M includes Fe; The M further comprises any one or a combination of at least two of Mn, Mg, Cr, Cu, Mo, Zn, Zr, Ti, B, Al, Nb or Si; The molar proportion of Fe in M is ≥90%.
3. The polyanion positive electrode material according to claim 1 or 2, characterized in that: The polyanion positive electrode material also includes a carbon coating layer, and the carbon coating layer is coated on the surface of the sodium iron phosphate pyrophosphate material; And / or, the compaction density of the polyanion positive electrode material is 1.95 g / cc-2.15 g / cc.
4. A method for preparing a polyanion positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing a sodium source, a phosphorus source and an iron source according to a formula amount to obtain a mixed ingredient; (2) mixing and drying the solvent and the mixed ingredients in step (1) to obtain a precursor material, and then sintering the precursor material once to obtain a primary sintered material; (3) mixing the mixed ingredients of step (1), the primary sintering material of step (2) and the solvent, drying and performing secondary sintering to obtain the polyanion positive electrode material; The secondary sintering temperature is ≤600°C.
5. The preparation method according to claim 4, characterized in that: In step (3), the mixed ingredients in step (1), the primary sintering material in step (2) and a solvent are mixed, wherein the mass ratio of the mixed ingredients in step (1) to the primary sintering material in step (2) is (0.2-10):
1.
6. The preparation method according to claim 5, characterized in that: In step (3), the mixed ingredients in step (1), the primary sintering material in step (2) and a solvent are mixed, wherein the mass ratio of the mixed ingredients in step (1) to the primary sintering material in step (2) is (0.5-3):
1.
7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (3), when the mixed ingredients in step (1), the primary sintering material in step (2) and the solvent are mixed, a carbon source accounting for 1 wt% to 10 wt% of the mixed ingredients in step (1) is also added; And / or, the drying methods in step (2) and step (3) are both spray drying; And / or, the mixing methods in step (2) and step (3) are both sand grinding, and the particle size D50 of the particles is sand grinding to 0.2 μm-0.6 μm.
8. The preparation method according to any one of claims 4 to 6, characterized in that: The secondary sintering temperature in step (3) is 450°C-600°C and the time is 2h-10h. And / or, in step (3), air flow crushing is further performed after the secondary sintering, and the air flow crushing is performed to particles with a particle size D50 of 1 μm-4 μm; And / or, in step (3), the mixed ingredients in step (1), the primary sintering material in step (2) and a solvent are mixed to obtain a mixed slurry having a solid content of 25 wt% to 55 wt%; And / or, the primary sintering temperature in step (2) is 300° C.-600° C., and the sintering time is 2 h-10 h.
9. The preparation method according to any one of claims 4 to 6, characterized in that: The primary sintering in step (2) includes two heating stages, firstly keeping the temperature at 450-460°C for 4h-7h, and then heating to 530-600°C for 3h-8h; And / or, when the solvent is mixed with the mixed ingredients in step (1) in step (2), a carbon source accounting for 2 wt%-8 wt% of the mixed ingredients in step (1) is also added; And / or, in step (2), the solvent is mixed with the mixed ingredients in step (1) to obtain a mixed slurry with a solid content of 15wt%-55wt%.
10. A battery, characterized in that: The battery comprises the polyanion positive electrode material according to any one of claims 1 to 3, or the polyanion positive electrode material prepared by the preparation method according to any one of claims 4 to 9.
Citation Information
Patent Citations
Carbon quantum dot and carbon quantum dot derivative coated iron magnesium sodium pyrophosphate composite material as well as preparation method and application of carbon quantum dot and carbon quantum dot derivative coated iron magnesium sodium pyrophosphate composite material
CN115411252A